Comparative analysis of coloured gangs in Cape Town and indigenous gangs on Canada’s prairies: connecting localized opposition to globalized grievances through street culture - Dziewanski, Dariusz (Critical criminology, 2023)
This paper undertakes a comparative analysis of Coloured gangs in Cape Town, South Africa, and Indigenous gangs in Canadian Prairie cities - Calgary, Winnipeg, Saskatoon, and others - looking at how members of each engage in street culture. It finds that street cultural participation in both settings is largely a collective response to globally recognizable - yet locally articulated - experiences with joblessness, over-incarceration, racialized poverty, and other forms of structural oppression. The paper uses life history research that was conducted with a sample of 24 gang members in South Africa and with another 53 from cities in Canada. Overall research findings are focused through the individual stories of Gavin and Roddy - research participants from Cape Town and Winnipeg, respectively - to provide personal and contextualized representations of broader key street cultural concepts and processes in each setting. The paper adds to a growing body of gang literature that draws comparisons across national contexts to show how street cultures are similarly used in an attempt to counteract experiences with vulnerability, exclusion, and alienation within distinct cultural contexts, socioeconomic situations, and colonial legacies.